Study of Earthquake Resistance of Buildings with Earthquick Foundations (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
A feature of the constructive solution of the building under study is the presence of a lower frame floor with switchable connections, which make it possible to change the rigidity of the lower tier by turning them off. The main structural elements of the adaptive seismic protection system were columns and buttresses. Switching elements are arranged between the heads of the upper and lower buttresses and are triggered when a certain level of movement of the lower tier of the building is reached. The work is devoted to the study of the dynamic behavior and seismic response of a building with switchable connections, in order to determine its rational dynamic characteristics.